2018
DOI: 10.1158/0008-5472.can-17-0491
|View full text |Cite
|
Sign up to set email alerts
|

Small-Molecule Inhibition of PD-1 Transcription Is an Effective Alternative to Antibody Blockade in Cancer Therapy

Abstract: The impact of PD-1 immune checkpoint therapy prompts exploration of other strategies to downregulate PD-1 for cancer therapy. We previously showed that the serine/threonine kinase, glycogen synthase kinase, GSK-3a/b, is a central regulator of PD-1 transcription in CD8 þ T cells. Here, we show that the use of smallmolecule inhibitors of GSK-3a/b (GSK-3i) to reduce pcdc1 (PD-1) transcription and expression was as effective as anti-PD-1 and PD-L1-blocking antibodies in the control of B16 melanoma, or EL4 lymphoma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
90
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(101 citation statements)
references
References 48 publications
(54 reference statements)
6
90
1
Order By: Relevance
“…Our findings also showed that GSK-3 inhibition operated primarily via a reduction in PD-1 transcription on CD8 + T cells (Taylor et al, 2016(Taylor et al, , 2018. We further showed that SMIs against GSK-3 are as effective as anti-PD-1 Abs in restricting B16 and EL-4 tumor growth in mice (Taylor et al, 2018).…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations
“…Our findings also showed that GSK-3 inhibition operated primarily via a reduction in PD-1 transcription on CD8 + T cells (Taylor et al, 2016(Taylor et al, , 2018. We further showed that SMIs against GSK-3 are as effective as anti-PD-1 Abs in restricting B16 and EL-4 tumor growth in mice (Taylor et al, 2018).…”
Section: Introductionsupporting
confidence: 67%
“…In this context, we have identified the enzyme glycogen synthase kinase-3 (GSK-3) as a major nexus in the control of PD-1 expression on T cells (Taylor et al, 2016). We also showed that small molecule inhibitors (SMIs) of GSK-3 can suppress tumor growth in a manner comparable to PD-1 Ab blockade (Taylor et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both approaches aim to block the checkpoint signals that attenuate the function of activated Teffs, thus releasing Teffs from negative feedback control (19). PD-1/PD-L1 blockade has previously been shown to effectively reduce growth of EL4-OVA, MC38, and LLC tumors (20)(21)(22), while anti-CTLA-4 has not been as successful, at least as a monotherapy in tumors lacking expression of a strongly immunogenic antigen (23)(24)(25). PI3Kδ D910A mice were injected with either LLC-OVA or MC38-OVA tumors, and treated with 3 doses of antibody against CTLA-4 or PD-L1 ( Figure 4A).…”
Section: Pi3kδ Inactivation Antagonized Enhancement Of Teff Responsesmentioning
confidence: 99%
“…Third, Li et al [76] showed that glycogen synthase kinase 3β (GSK3β) interacts with PD-L1 and can induce phosphorylation-dependent proteasome degradation of PD-L1. A study by Taylor and colleagues [77] also reported that GSK3β inhibitors can downregulate PD-1 expression and enhance CD8+ T-cell function in cancer therapy. Thus, the combination of tideglusib, a GSK3β inhibitor, with anti-PD-1 therapy could be a promising strategy for melanoma treatment.…”
Section: Resultsmentioning
confidence: 99%